Amylase of Trichoderma viride - Khan, M.R.; Khan, S.A. (Asian Journal of Chemistry, 2012)
Optimal production of amylase by Trichoderma viride and its study of some crude state characteristics were carried out. The organism was grown in 3 % wheat bran medium containing 1 % glucose as carbon source and later 1 % starch as carbon source. The growth was fairly large and enzyme production was fairly high when glucose was used as source of carbon. In case of starch as carbon source, the growth was very small and the quantity of amylase produced was also small. The comparison showed that glucose is a good carbon source for production of amylase by Trichoderma viride as compared to starch.